Spatial confinement of sliver nanoparticles in nitrogen-doped carbon framework with high catalytic activity and long-term cycling - Yang, Meng; Zhang, Jingwu; Wang, Jinming; Gao, Wei; Liu, Di; Li, Lanjie; Wang, Yimin; Peng, Qiuming (Frontiers in Energy Research, 2023)
The development of efficient, economical and stable oxygen reduction reaction (ORR) electro-catalysts is crucial to energy storage-conversion technology. To reducing metal dimension to nanosize is a promising approach to maximize its efficiency, whereas the migration and aggregation of nanoparticles have severely hampered their large-scale applications. Herein, we report a new catalyst of N-doped carbon-coated Ag nano-particles (Ag NP@N-C), wherein Ag nanoparticles are confined by N-doped carbon framework. This as-synthesized Ag NP@N-C exhibits excellent ORR performance with a half-wave potential of 0.83 V and a limit-current density of 7.03 mA cm-2 in an alkaline medium. More importantly, its durability (cycling for 3600 minutes), methanol resistance ability in alkaline solutions and catalytic properties in rechargeable zinc-air battery outperforms those of commercial Pt/C catalyst and other similar Ag-based catalysts reported so far. The main reason stems from the fact that the interaction between Ag nanoparticles and the support of N-doped carbon can be enhanced by the co-work of pyridine nitrogen and carbon vacancy, rationalizing uniform dispersion of Ag particles. Taking into account its simplicity and high electrochemical properties, we believe that spatial confinement might take an effective trajectory to develop new and large-scale catalysts.